2010
DOI: 10.1016/j.concog.2009.12.019
|View full text |Cite
|
Sign up to set email alerts
|

The relation between consciousness and attention: An empirical study using the priming paradigm

Abstract: Dehaene, Changeux, Naccache, Sackur, and Sergent (2006) and Koch and Tsuchiya (2007) recently proposed taxonomies that distinguish between four processing states, based on bottom-up stimulus strength and top-down attentional amplification. The aim of the present study was to empirically test these processing states using the priming paradigm. Our results showed that attention (prime attended or not) and stimulus strength (prime presented subliminally or not) significantly modulated priming effects: either rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…In line with their position, there is good evidence that attentional processes, as defined above, can operate without the attended stimuli reaching consciousness (Bressan and Pizzighello, 2008; Kentridge et al, 2008; Bussche et al, 2010; Tapia et al, 2010). For example, Kentridge et al (2008) demonstrated that attention can enhance the processing of unconscious targets: incongruent or congruent colored disk primes, made invisible by metacontrast masking, were followed by a subsequent visible colored annulus.…”
Section: The Overlap Between Attention and Consciousnessmentioning
confidence: 76%
“…In line with their position, there is good evidence that attentional processes, as defined above, can operate without the attended stimuli reaching consciousness (Bressan and Pizzighello, 2008; Kentridge et al, 2008; Bussche et al, 2010; Tapia et al, 2010). For example, Kentridge et al (2008) demonstrated that attention can enhance the processing of unconscious targets: incongruent or congruent colored disk primes, made invisible by metacontrast masking, were followed by a subsequent visible colored annulus.…”
Section: The Overlap Between Attention and Consciousnessmentioning
confidence: 76%
“…Behavioral (Naccache et al, 2002; Ansorge and Neumann, 2005; Melcher et al, 2005; Sumner et al, 2006; Kentridge et al, 2008; Finkbeiner and Palermo, 2009; Tapia et al, 2010; Van den Bussche et al, 2010) and neuronal (Kiefer and Brendel, 2006) non-conscious priming is enhanced by spatial (Kentridge et al, 2008; Finkbeiner and Palermo, 2009; Van den Bussche et al, 2010), feature-based (Melcher et al, 2005; Tapia et al, 2010), or temporal (i.e., cueing when the prime or targets appear) (Naccache et al, 2002) attention. So far, there is no evidence that object-based attention can give rise to non-conscious priming (Tapia et al, 2010).…”
Section: Attention Without Consciousnessmentioning
confidence: 99%
“…Although the influence of unconscious primes has often been thought a static, uncontrollable process, recently research pointed out that it can be influenced by top-down aspects such as task demands (Norris and Kinoshita, 2008; Martens et al, 2011), attentional focusing (Van den Bussche et al, 2010), and temporal attention (Naccache et al, 2002). Martens et al (2011) used an induction task to activate one of two task sets.…”
Section: Introductionmentioning
confidence: 99%
“…However, when exactly the same prime–target pairs were used, but now the task was to decide whether the target was the same as a probe, unconscious priming was also observed for non-words. Van den Bussche et al (2010) showed that spatial attention is a prerequisite for subliminal stimuli to be processed. When attention was allocated to another location, primes had no influence on the processing of the target.…”
Section: Introductionmentioning
confidence: 99%